Computational investigation of nasal surface coverage from squeeze bottle and Neti Pot saline irrigation flow. (December 2022) - Salati, Hana; Khamooshi, Mehrdad; Fletcher, David F.; Inthavong, Kiao
Highlights: Computational fluid dynamics was used to study nasal irrigation in a healthy patient using different delivery devices. Ansys Fluent 2021R1 was used to perform a transient multiphase flow simulation. Squeeze bottle irrigation profile was obtained from physical experiments. A Neti Pot device was attached to the nostril to represent the irrigation event using a gravity-dependent device. Abstract: Background and objective: Nasal saline irrigation is a common therapy for inflammatory nasal and paranasal disease or for managing post nasal and sinus surgery recovery. Two common irrigation devices include the netipot and squeeze bottles, where anecdotally, these devices alleviate congestion, facial pain, and pressure. However, a quantitative evaluation of these devices' performance and the fluid dynamics responsible for the irrigation distribution through the nose is lacking. This study tracked the liquid surface coverage and wall shear stresses during nasal saline irrigation produced from a Neti Pot and squeeze bottle. Methods: This study used transient computational fluid dynamics (CFD) simulations to investigate the saline irrigation flow field in a subject-specific sinonasal model. The computational nasal cavity model was constructed from a high-resolution computed tomography scan (CT). The irrigation procedure applied a head position tilted at 90° forward using an 80 ml squeeze bottle and 120 ml Neti Pot. Results: The results from a single sinonasal model demonstrated that the Neti Pot irrigation was more effective in delivering saline solution to the nasal cavity on the contralateral side of irrigation due to typically larger volumes but at the expense of reduced flow and shearing rates, as the flow entered under gravitational forces. The squeeze bottle irrigation provided greater surface coverage on the side of irrigation. Conclusions: The results from the single patient model, demonstrated the Neti Pot increased surface coverage in the paranasal sinuses. Reducing the jet diameter may aid the direct targeting of a specific region at the side of irrigation by preventing the impingement of the jet to the nasal passage surface and redirection of the flow. Evaluating this performance across a wider cohort of patients can strengthen the findings.